(untitled) (MAUSAM, 1978)
A theoretical study of the interaction or remote effects on the monsoon system is described. Such effects, in particular the cross-equatorial influence of the rapidly evolving southern hemisphere equinoctial circulation in the late northern hemisphere spring and again in the fall, have been speculated from observation. To study such interaction, a primitive barotropic model is developed which contains a basic flow in the equatorial regions which is a function of both latitude and longitude. Such a flow contains the influence of the large-scale stationary eddies of low-latitudes which has the effect of producing a’ ’critical latitude" that is also a function of both longitude and latitude, In this manner equatorward propagating energy from mid-latitude disturbances has the opportunity to propagate through the equatorial regions and thus modify the basic structure of the monsoon regime.